Faktor yang Berhubungan dengan Kejadian Stunting pada Balita Usia 24-59 Bulan di Wilayah Kerja Puskesmas Baa Kabupaten Rote Ndao - Iksan Kaleb Adu; Pius Weraman; Deviarbi S. Tira (Media Kesehatan Masyarakat, 2021)
Stunting describes the unfulfilled intake of nutrients needed by toddlers that has been going on for a long time since the fetus is in the womb until the child is born and the first 2 years of the child's life. The aim of this study was to analyze the factors associated with the incidence of stunting in toddlers aged 24-59 months. This research is an analytic survey research based on a cross sectional study. The sample in this study amounted to 103 toddlers who were selected by simple random sampling technique. This research was conducted from September to October 2020. Data were collected by conducting interviews, observations, filling out questionnaires and also documentation. In the bivariate analysis the chi-square test was used and the multivariate analysis used the multiple logistic regression test. The results of multivariate analysis showed a significant relationship between exclusive breastfeeding (p-value = 0.003), feeding patterns (p-value = 0.010), maternal education (p-value = 0.019) and a history of LBW (p-value = 0.000). LBW history is the factor most associated with the incidence of stunting. It is hoped that expectant mothers and mothers will understand correctly about the problem of stunting, its causes and protection factors so that efforts to prevent and overcome stunting can be carried out. It is hoped that the Puskesmas will continue to make health promotion efforts regarding stunting and the factors that influence it.